Rancang Bangun Sistem Pendeteksi Ketinggian Tanah, Tekanan Udara Dan Suhu Serta Monitoring Kesehatan Pada Pendaki Dalam Pendakian Gunung Dengan Notifikasi Telegram Berbasis Arduino Mega 2560 - Andrica Putra, Octa; Andrianof, Harkamsyah; Pramana Gusman, Aggy (Jurnal Sains Informatika Terapan, 2023)
Mountain climbing requires high vigilance and preparedness related to various conditions that may be faced. In order to improve the safety and comfort of climbers, this research designs and builds a system for detecting ground level, air pressure and temperature as well as monitoring the health of climbers with Telegram notifications based on Arduino Mega 2560. This system uses Arduino Mega 2560 technology, a board-based micro-controller that can be programmed for various applications. The system is able to detect and monitor ground level, air pressure, temperature and climbers' health conditions in real-time. In addition, the system is also integrated with Telegram, a popular communication platform. The Telegram notification facility is used to send information and alerts from the system to climbers or support teams. Thus, preventive measures or emergency treatment can be taken immediately if there is a significant change in conditions. With the design of this system, it is expected that the safety and comfort of mountain climbers can be better guaranteed, and the risk of accidents and unwanted health conditions can be minimized. This research contributes to the development of supporting technology for safer and more comfortable mountaineering activities